2022
DOI: 10.3389/fped.2022.813486
|View full text |Cite
|
Sign up to set email alerts
|

Explicating Child-Driven Patterns of Parent-Child Responsivity in Fragile Families: A Longitudinal Approach

Abstract: It has been well-established that development occurs in the context of a transactional framework, with bidirectional parent-child interactions influencing both proximal and distal outcomes. In particular, child vocabulary development is sensitive to parenting qualities including warmth, sensitivity, and control as well as parental stimulation including language input and access to learning enrichment activities. Similarly, these parenting qualities are influenced by and influence children's development of pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 94 publications
(109 reference statements)
1
2
0
Order By: Relevance
“…Proximal responsivity was associated with a mix of maternal-reported perceptions and behaviors, ranging from mothers feeling stressed and concerned that their child was not eating enough to talking and being in a happy mood while their child was eating. The finding that maternal concerns about children’s intake coupled with feelings of stress were associated with proximal responsivity is consistent with reports that child behaviors and maternal perceptions about children’s growth, health, and temperament drive maternal-child responsivity [ 4 , 30 ]. Mothers’ happy mood and talking during meals may reflect positive feelings of being engaged in their child’s feeding, even in the face of stress and concern.…”
Section: Discussionsupporting
confidence: 87%
“…Proximal responsivity was associated with a mix of maternal-reported perceptions and behaviors, ranging from mothers feeling stressed and concerned that their child was not eating enough to talking and being in a happy mood while their child was eating. The finding that maternal concerns about children’s intake coupled with feelings of stress were associated with proximal responsivity is consistent with reports that child behaviors and maternal perceptions about children’s growth, health, and temperament drive maternal-child responsivity [ 4 , 30 ]. Mothers’ happy mood and talking during meals may reflect positive feelings of being engaged in their child’s feeding, even in the face of stress and concern.…”
Section: Discussionsupporting
confidence: 87%
“…It is well-known that parenthood is a substantial life change which can be stressful, particularly if children are diagnosed with physical or mental disabilities (Hayes & Watson, 2013). Developmental transition periods such as middle childhood can be of particular importance for child driven-effects (Blume et al, 2022;Yan & Ansari, 2016). Jiang et al (2022) found that parenting stress was largely predicted by child problem behaviours, however, there was a reciprocal association in early childhood, with internalising behaviour being specifically larger in effect size and more prevalent over time compared to externalising in disadvantaged families (a similar cohort to our study in some aspects).…”
Section: Trait-like Associations (Between-person)mentioning
confidence: 99%
“…As such, parental sensitivity is more likely in the context of an infant who frequently initiates conversation with their parents. Transactional links between parental sensitive responding and children's developing social competence have been documented in early and middle childhood (e.g., Blume et al., 2022; Guo et al., 2023). These patterns of associations also apply to early parent‐infant interactions.…”
Section: Introductionmentioning
confidence: 99%